Efficient TALEN-mediated myostatin gene editing in goats. Issue 1 (December 2016) - Yu, Baoli; Lu, Rui; Yuan, Yuguo; Zhang, Ting; Song, Shaozheng; Qi, Zhengqiang; Shao, Bin; Zhu, Mengmin; Mi, Fei; Cheng, Yong
Abstract Background Myostatin (MSTN ) encodes a negative regulator of skeletal muscle mass that might have applications for promoting muscle growth in livestock. In this study, we aimed to test whether targetedMSTN editing, mediated by transcription activator-like effector nucleases (TALENs), is a viable approach to create myostatin-modified goats (Capra hircus ). Results We obtained a pair of TALENs (MTAL-2) that could recognize and cut the targetedMSTN site in the goat genome. Fibroblasts from pedigreed goats were co-transfected with MTAL-2, and 272 monoclonal cell strains were confirmed to have mono- or bi-allelic mutations inMSTN . Ten cell strains with different genotypes were used as donor cells for somatic cell nuclear transfer, which produced three cloned kids (K179/MSTN−/−, K52-2/MSTN +/−, and K52-1/MSTN +/+ ). Conclusions The results suggested that the MTAL-2 could disruptMSTN efficiently in the goat genome. The mutated somatic cells could be used to produceMSTN -site mutated goats without developmental disruption. Thus, TALENs is an effective method for accurate genome editing to produce site-modified goats.